Students’ Perception and Usage of ChatGPT in Language Translation Activities: Evidence from EFL Learners - Febri Yonanda Yovi; Veni Roza; Widya Syafitri (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
The integration of Artificial Intelligence (AI) into language learning has transformed the way students engage in translation activities. One of the most widely used AI tools is ChatGPT, which offers various features that support language learning and translation. This study aimed to investigate students' usage of ChatGPT in language translation activities and explore their perceptions of its benefits and limitations. The study employed a quantitative descriptive research design and involved 41 students of SMP Al-Ishlah Bukittinggi, with 20 students participating in the instrument try-out for reliability testing and the remaining 21 students serving as the actual participants. Data were collected through a questionnaire distributed via Google Forms and analyzed using descriptive statistics. Prior to data collection, the questionnaire was reviewed by an English teacher for clarity and relevance, and its reliability was tested using Cronbach's Alpha (α = 0.735), indicating an acceptable level of internal consistency. The findings revealed that students generally held positive perceptions toward ChatGPT, with an overall mean score of 3.48 (Agree), and recognized its usefulness in supporting translation activities. Students reported that ChatGPT helps them understand difficult vocabulary and sentence structures, learn new vocabulary, improve translation performance, and support language learning, although they remained critically aware of its occasional inaccuracy and did not strongly prefer it over other translation tools. In conclusion, ChatGPT has considerable potential as a supplementary tool for language translation and English language learning. However, its effectiveness depends on students' ability to use the technology critically and responsibly. Therefore, ChatGPT should be viewed as a complementary educational resource rather than a replacement for traditional learning methods that are still usable.